Exploring Creativities through Rhythm, Drama and Movement: Intensive Workshop Series Conducted with Seven Tanzanian Youth in August 2017 - Ndale, Megan (Taideyliopiston Sibelius-Akatemia, 2018)
Finding the balance between working collaboratively as part of a community, and exploring one’s own, individual creative instincts and abilities can be difficult in artistic and educational settings. Could the arts be a key to unlock the flow of individual creativities and expression, specifically amidst the conditioning of the Tanzanian Secondary School system? In this paper the author explores the concepts of creativities and the community arts through a reflection of the pedagogical project “Camp for Creativity” conducted with seven Tanzanian youth. Aiming to develop creative skills, the camp consisted of day workshops exploring various creative skills, such as rhythmic compositional creativity, dance, drama, and making instruments out of everyday items. The camp ended in a video-recorded performance open to the public. After five days of workshops, this project confirmed the author’s speculations on how these activities affect the participant’s personal creativities in various situations, during interviews the participants mentioned that confidence and self worth were the main things they took away, as well as a newfound sense of discovery in themselves and the world around them. This project establishes the importance of similar projects in the future as a way to kick-start individual creativity and confidence in participants.
Keywords: Glomas